(untitled) (Progressive Agriculture, 2013)
The present study was undertaken for callus induction and subsequent plantlet regeneration in blackgram. The study comprised of experiments for callus initiation, shoot regeneration and plantlet formation from cotyledon, hypocotyl, root tip and shoot tip explants. The effects of explants and different concentrations and combinations of BAP (0.0, 1.0, 2.5, 5.0 and 10 mg L-1) and NAA (0.0, 0.5, 1.0, 1.5 and 2.0 mg L-1)) on callus induction were investigated first. Among the explants, hypocotyls showed the best performance in callus formation (92.33%) when cultured on MS medium supplemented with 2.5 mg L-1) BAP and 1.5 mg L-1) NAA followed by cotyledon, shoot tip and root tip explants, respectively. The height percentage of shoot regeneration from the calli derived from hypocotyls (56.33%) was achieved in MS medium supplemented with 3.0 mg L-1) BAP and 0.3 mg L-1) NAA and 0.5 mg L-1) GA3. Calli from other explants had no shoot regeneration. The regenerated shoots were transferred to rooting medium supplemented with different concentrations of IBA and NAA. The high frequency (100 %) of rooting was observed with MS medium supplemented with 0.5 mg L-1) IBA. The rooted plants were transferred to pots for hardening. DOI: http://dx.doi.org/10.3329/pa.v19i2.16917 Progress. Agric. 19(2): 27 - 35, 2008